The effect of the sweepback of delta wings on the performance of an aircraft at supersonic speeds - Robinson, A.; Davies, F.T. (College of Aeronautics, Cranfield, 1947)
The variation with sweepback of total drag of an aircraft in level flight at supersonic speeds is calculated. It is shown that sweepback is not uniformly beneficial, but that in general the optimum amount of sweepback depends in the design speed and altitude.